MORPHOFUNCTIONAL ECOLOGY OF SEEDLINGS FOUND IN A TROPICAL RAINFOREST SEED BANK, IN THE NORTHEAST OF BRAZIL - Silva, Joselane Príscila Gomes da; Marangon, Luiz Carlos; Feliciano, Ana Lícia Patriota; Ferreira, Rinaldo Luiz Caraciolo (Floresta, 2021)
The aim of this study was to evaluate the identification and floristic composition of seedlings of tree species, located in the soil seed bank of a remnant of the Dense Ombrophilous Forest of the Lowlands, in the Northeast of Brazil, from a morphofunctional ecology standpoint. A hundred and fifty two soil samples (0.2 m x 0.15 m x 0.05 m) were taken from a forest remnant, stored in polyethylene bags, identified and then taken to the Forest Nursery at the Federal Rural University of Pernambuco, where they were placed in polyethylene boxes under a 70% shade cloth and evaluated daily for a period of seven months. The seedlings emerged were photographed, separated into morphospecies, identified at the family and gender level and, when possible, at the species level. The density and absolute frequency, as well as the successional and morphological classification of the seedling cotyledons were estimated. In total, 1,577 seedlings of 31 morphospecies were cataloged. Melastomataceae was the family that presented the greatest richness, representing 48% of the species identified. The average density was 344.62 seeds.m-2, with higher densities for species of the family Melastomataceae, together with Maprounea guianensis and Cecropia palmata. There was a predominance of seedlings with epigeal and phanerocotylar germination, and with foliaceous cotyledons, corresponding to 93.56%. The seed bank was composed, predominantly, by pioneer species such as Cecropia palmata, Henriettea succosa, Miconia hypoleuca and Miconia tomentosa. Seedlings with epigeal germination, foliaceous and phanerocotylar cotyledons predominated for being easily established in more open areas.